Rare case of phenytoin induced acute generalized exanthematous pustulosis with cerebellar syndrome - Pravin U Shingade; Vaishali Wankhede; Pritam S Kataria; Nitin Sonone (Wolters Kluwer Medknow Publications, 2014)
Acute generalized exanthematous pustulosis (AGEP) is a rare drug induced cutaneous hypersensitivity reaction characterized by sudden onset of fever with sterile pustules overlying an erythematous skin occurring all over the body. The offending drugs are usually B-lactams and macrolides.Among anticonvulsants carbamazepine and Phenobarbital are commonly associated with AGEP. Only one case of phenytoin induced AGEP has been reported in literature. We present a rare case of AGEP with cerebellar syndrome occurring after receiving loading dose of phenytoin.